CATHOLICISM AND DEMOCRACY: PAST AND PRESENT - Himes, Kenneth R. (Asian Horizons, 2020)
This essay examines the record of the Church’s teaching on political democracy from the 19th to 21st centuries. There will be a focus on the Vatican, the papacy, and Italian politics for constructing the narrative since the Church’s direct investment in temporal politics and institutional self-interest is clear in the story of Italian democracy. There will also be an overview of the modern papacy’s evolution in its assessment of political democracy to the point where opposition has become active support and commendation.